Analysis of Communication Integrity on Loyalty Mediated by Trust at the UPTD Lanjut Usia Binjai - Sitompul, Agriani Sartika; Surya, Elfitra Desy; B, Mesra; Erwansyah, Erwansyah (Blantika: Multidisciplinary Journal, 2025)
The objective of this research is to study the influence of communication integrity on the loyalty of the residents of UPTD Lanjut Usia Binjai, with trust acting as the mediator. The study employed the quantitative method under Structural Equation Modeling–Partial Least Squares (SEM-PLS). The outer model test results indicate that all the indicators are valid and reliable. The inner model test result shows that communication integrity significantly affects trust and loyalty, while trust significantly affects loyalty. The test results on mediation show that trust partially mediates communication integrity's influence on loyalty. The R-squared measure of 0.750 for loyalty and 0.817 for trust indicates the good explanatory capability of the model. The significance of this study is the realization that there is the need to strengthen communication integrity to boost trust and loyalty among the elderly residents. The implication of these findings underscores the necessity for the UPTD management to proactively build and maintain communication integrity in every interaction, in order to foster trust which ultimately forms a solid foundation for sustainable loyalty among the elderly residents.